Ordered porous structure hybrid films generated by breath figures for directional water penetration. Issue 107 (19th October 2015) - Guo, Tianqi; Han, Keyu; Heng, Liping; Cao, Moyuan; Jiang, Lei
Abstract : A highly ordered open-pore hybrid film was fabricated by controlling the substrate roughness and wettability. The composite with different wettability on the two side resulted in an attractive unidirectional water-penetration function (see figure). Abstract : A highly ordered open pore honeycomb-structured hybrid film was fabricated by controlling substrate roughness and wettability with the breath figure (BF) method. This composite consists of a porous hydrophobic polyimide (PI) film and a hydrophilic anodic aluminum oxide (AAO) film. The difference between hydrophilic-hydrophobic surfaces yielded an attractive directional water-penetration function. These findings may lead to new applications for honeycomb-structured composites with directional water functionality in fields such as directional drug delivery, biosensors and molecular filtration.